THE MULTIFARIOUSNESS OF OPERATIONS RESEARCH IN SOLVING COMPLEX NATIONAL PROBLEMS (A TACTICAL APPROACH TO INSURGENCY IN NIGERIA) - Ayodeji Ojo, Oloruntuyi; Solomon Chidi, Nwalozie (IJRDO - Journal of Business Management, 2016)
Operations research has aided in divers capacity the decision making process of military and non-military operations in war times across the globe but not much has been recorded in the application O.R. model to socio-economic problem like Insurgency. This study aimed at minimizing insurgency objective function z = xi+ xj by reducing the average number of successful attacks and death resulting from insurgency. The model simplifies the mathematical symbolization of the social violence by considering the rate of occurrence of the incidents as a determinant of the rate of victimization/death. Findings reveal that there is inverse relationship between insurgency ‘z’ and solution factor ‘f’. That is as the decision variables are rightly implemented or channeled in the appropriate direction, the number of attack of the insurgents and the average number of victims reduces simultaneously. In conclusion the strategic application of O.R. would eradicate insurgency in Nigeria.